A república brasileira e a definição de uma língua nacional : as posições discursivas de Olavo Bilac e Mário de Andrade - Bornemann, Neila Barbosa de Oliveira (2019)
This is a research developed in the scope of a Doctoral Program in Language Studies at the Federal University of Mato Grosso (UFMT), with the aim of analyzing the interdiscursive relations between the separatist and legitimist discourses in relation to the question of the national language. It is focused the Brazilian literary scene through two contiguous and antagonist movements, Parnassianism and Modernism, represented in this investigation by Olavo Bilac and Mário de Andrade respectively. The study will be theoretical-methodologically based on the French discourse analysis, as conceived and practiced by Michel Pêcheux, Michel Foucault, Jean-Jacques Courtine, Dominique Maingueneau, Eni Orlandi, Sírio Possenti, among others. The starting point will be the research of the archives of Olavo Bilac and Mário de Andrade, through a procedure of reading, selecting and cutting out formulations/utterances in which the National Language issue is thematized. These cuttings, grouped into paraphrastic families, will constitute discursive corpora, whose analysis and interpretation will be based on the concepts of utterance and formulation, discursive formation, inter-discourse (and their correlates, Maingueneau’s bias: interincomprehension, translation and simulacrum) and subject-form. The aim is to understand the ideology of the Parnassian and Modern movements, in relation to the definition or constitution of a national language in the context of a newlycreated Republican State; to outline the semantics of the legitimist and separatist discourses regarding the national language; to grasp at the linguistic surface level, material marks of the polemic between the separatist and legitimist discourses; to understand how the interincompreenhension, the translation of the discourse of the other and the production of simulacra are materialized, with the legitimist and separatist discourses alternating in the position of the agent discourse and the patient discourse. When Olavo Bilac and Mário de Andrade are compared, the former a legitimist subject and the latter a separatist subject, it is perceived that the only point of convergence between them is the equation nationnational language. However, they differ in the way of solving the equation: the legitimist solves the equation as Brazil-Portuguese language and the separatist, as Brazil-Brazilian language/speech. If, among the legitimists, the linguistic dilemma presented was that of ideologically unifying the Brazilian republic by the officialization of Portuguese as a national language, among the separatists, was that of making Brazilian the national language of the republic, to give rise to the Brazilian civilization amid the other civilizations.